The UK tax system and the environment - Andrew Leicester (Institute for Fiscal Studies (IFS), 2006)
This report takes a broad overview of the UK environmental tax system as it exists in 2006. It aims to bring together evidence and data from a range of sources to provide a central source of information about the existing environmental tax system, alongside discussion of the key principles of the debate around using taxes and other economic instruments for environmental goals. The report assesses broad trends over time - both in environmental tax revenues and in greenhouse gas emissions, the latter with respect to the government's own emissions-reduction targets and the Kyoto Protocol. It also examines current measures case by case, considering and commenting on the history, motivation, design and implementation of each tax, evidence on the effects (both intentional and perhaps unintentional), trends in revenue and, where important, any distributional implications. Taxes are considered under three broad headings: transport, natural resources and energy. The report looks at new taxes designed explicitly for environmental ends (such as the climate change levy), taxes that were not environmental in intention but have environmental consequences (such as fuel duty), taxes that were altered to incorporate a more obvious environmental objective (such as changes to VAT) and non-tax measures that nevertheless provide economic incentives for pollution reduction (such as the UK and EU Emissions Trading Schemes). The report is not designed to be prescriptive - it does not suggest or encourage that particular policies be changed or introduced, nor does it try to estimate how far current policy will go in the future to meet environmental objectives. Rather, it is designed as a factual overview of where current policy has taken us. However, it does consider some possible future reforms to the environmental tax system - road user charging, carbon taxes and taxes on packaging waste (plastic carrier bags) - that have been suggested. In a report of this nature, it is, of course, extremely difficult to summarise the findings as a whole for each part of the environmental tax system. Some of the key results, both general and for particular tax measures, are, however, presented here.
Keywords: 330